If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -11z + 2z = -10z Combine like terms: -11z + 2z = -9z -9z = -10z Solving -9z = -10z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '10z' to each side of the equation. -9z + 10z = -10z + 10z Combine like terms: -9z + 10z = 1z 1z = -10z + 10z Combine like terms: -10z + 10z = 0 1z = 0 Divide each side by '1'. z = 0 Simplifying z = 0
| 4x+14=-2x-8 | | 3x-3+5=37 | | 8m-10=5-2m | | -4a+6a=7a | | 3x(x+1)+5=0 | | 2-11z=-10 | | 2-11z=-11 | | 2x+4=8x-50 | | ln(x+1)=0 | | x+99=-2912x-99123 | | 3(x+1)+5=0 | | x(x+2)=99 | | 7m+6m-4=63 | | -45=10t+-5t^2 | | -45=10t*-5t^2 | | 3x-2=6x+20 | | 4x+8=x^2+11x | | 3(x+5)+2=-11-4x | | -y-8=-9 | | -8(2y-4)=9(4-2y) | | -4(7y+9)=(3-5y)3-4y | | 5a^2-19a=15 | | 2x=x+25 | | 22+3(a+6)=-4(3a+5) | | 3(x+2)+5=0 | | 4x-3+6x+3=90 | | -2+6j=-20 | | 6t+12=42 | | 3b=7a | | 7a=3b | | x(4-5)=114 | | 4x+(43x)*(3-x)=5+x |